A Study on Interdisciplinary Conceptual Integration of Supply Chain Management and Talent Management - Srinivas, Kolachina; Raj, K Bhavana (ExcelingTech, 2019)
Managing the intangible component of workforce called talent has become one of the critical challenges for many organizations. Various strategies framed by them, to bridge the gap between demand and supply of talent, are becoming rather obselete in no time owing to the influence of various factors in the ever dynamic and competitive business environment. The possessed skills of the employees have to be matched with that of needed by the organization wherein any mismatch may lead to the cost of loosing a potential intellectual source. Suppy Chain Management is a discipline that ably focusses on managing the supply of goods with the demand from consumers. Borrowing the conceptual flavour of Supply Chain Management to Talent Managent, a novel and agile approach called Talent Supply Chain Management has evolved. The article aims at exploring the new concept by having a glance at the possible comparison of concepts from mutual disciplines. Besides exploration, certain frameworks and models are also discussed herewith which, upon successful adoption and implementation, can enhance the efficiency of talent management process.